Issues Faced by Prosthetists and Physiotherapists During Lower-Limb Prosthetic Rehabilitation: A Thematic Analysis - Turner, Shruti; Belsi, Athina; McGregor, Alison H. (Frontiers in Rehabilitation Sciences, 2022)
Successful prosthetic rehabilitation is essential to improve the physical and mental outcomes of people with lower-limb amputation. Evaluation of prosthetic services from a prosthesis user perspective have been published and commissioned by the national bodies, however, the perspectives of clinicians working with service users during rehabilitation have not to date been sought. We sought to determine factors impacting lower-limb prosthetic rehabilitation from a clinician’s perspective to inform studies focusing on prosthetic and socket design and fitting. Six clinician (2 prosthetists, 4 physiotherapists) interviewees were self-selected from a survey exploring issues and frustrations during lower-limb prosthetic rehabilitation. Semi-structured interviews explored the impactors on and frustrations with rehabilitation and the prosthetic socket. A thematic analysis was subsequently conducted to identify themes in the responses. Five themes were identified: Service Disparity, Body Impactors, Consequences of Ill-Fit, Prosthesis Irritants, and Limitations of Practice. Each theme, though distinct, relates to the others either as a cause or consequence and should be viewed as such. Addressing the themes will have benefits beyond the issues addressed but also expand into the other themes. This study provides an insight into the clinician perspectives on lower-limb prosthetic rehabilitation, which has not been formally documented to date.